2014
DOI: 10.1017/jfm.2014.546
|View full text |Cite
|
Sign up to set email alerts
|

Steady streaming of a viscoelastic fluid within a periodically rotating sphere

Abstract: Motivated by understanding mass transport processes occurring in the vitreous chamber of the eye, we consider the steady streaming component of the flow generated in a viscoelastic fluid contained within a hollow, rigid sphere performing small-amplitude, periodic, torsional oscillations about an axis passing through its centre. The problem is solved semi-analytically, assuming that the amplitude of the oscillations is small. The paper extends the work by Repetto et al. (J. Fluid Mech., vol. 608, 2008, pp. 71-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The latter changes in space and time and the complex modulus does so accordingly. This effect is not accounted for in theory and may play a more important role than nonlinearity as discussed by Repetto et al [ 17 ], who showed that nonlinear corrections to the azimuthal velocity profiles would appear at the third order (in the small strain) and it is thus likely to contribute little to the measured velocity profiles.
Fig.
…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The latter changes in space and time and the complex modulus does so accordingly. This effect is not accounted for in theory and may play a more important role than nonlinearity as discussed by Repetto et al [ 17 ], who showed that nonlinear corrections to the azimuthal velocity profiles would appear at the third order (in the small strain) and it is thus likely to contribute little to the measured velocity profiles.
Fig.
…”
Section: Resultsmentioning
confidence: 98%
“…This is because considering for instance the case of linearly viscoelastic fluids, one should preserve between the prototype and the scaled model the values of two dimensionless parameters, e.g. the Womersley number and the ratio between the elastic and viscous components of the fluid (see for instance [ 17 ]). Once a certain fluid has been chosen for the experiments this should be accomplished by changing the model rotation frequency.…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of steady flows produced by oscillating bodies in a fluid is a well-known phenomenon in fluid mechanics and is referred to as steady streaming, which occurs in both viscous 25,26 and viscoelastic fluids. 27 Cavitation has never been observed.…”
Section: Two-dimensional Flow Fieldsmentioning
confidence: 99%
“…Extensive studies of solute dispersion in microchannels with the interphase transport were carried out from the perspectives of the solute separation efficiency [19,23,24] or the solute dispersion theory [25][26][27][28][29]. Also, the dispersion of reactive solutes [29][30][31][32], non-Newton fluids [33,34], and stratified liquids [35] has been widely investigated. These studies obtain numerous expressions of the dispersion coefficient for varying flow fields and wall interactions, which are summarized in Ref.…”
Section: Introductionmentioning
confidence: 99%